Integrating Faith and Ethics in Police Education: A Phenomenological Study on Character Cultivation at the Indonesian Police Academy - Susilo, Sigit; Pramono, Suwito Eko; Sutarto, Joko (Universitas Negeri Semarang, 2024)
This study investigates the management of cultivating the character of “kebhayangkaraan” based on faith and devotion among Level I cadets at the Indonesian Police Academy. Employing a qualitative phenomenological approach, the research was conducted at the Level I Battalion in Semarang, utilizing purposive sampling. Data were collected through in-depth interviews, engaged observation, and documentation, and validated using triangulation of sources and methods. Data analysis followed the Miles and Huberman framework. The findings highlight the importance of instilling faith and devotion in cadets who transition from civilian life to a police institution. The academy's curriculum, enriched with comparative religious studies, ethical applications, and reflective practices such as meditation and community engagement, effectively cultivates individuals who uphold law with justice, empathy, and faith. Caregivers play a pivotal role, using tailored parenting strategies to reinforce these virtues. This study contributes to the field by demonstrating how a structured approach to religious and ethical education can enhance the moral integrity and professional competence of future police officers, thus providing a model for similar institutions aiming to integrate faith-based character building into their training programs.